Insulin-like growth factor pathway genes and blood concentrations, dietary protein and risk of prostate cancer in the NCI Breast and Prostate Cancer Cohort Consortium (BPC3). - Tsilidis, K; Travis, R; Appleby, P; Allen, N; Lindström, S; Albanes, D; Ziegler, R; McCullough, M; Siddiq, A; Barricarte, A; Berndt, S; Bueno-de-Mesquita, H; et al. (2013)
It has been hypothesized that a high intake of dairy protein may increase prostate cancer risk by increasing the production of insulin-like growth factor 1 (IGF-1). Several single nucleotide polymorphisms (SNPs) have been weakly associated with circulating concentrations of IGF-1 and IGF binding protein 3 (IGFBP-3), but none of these SNPs was associated with risk of prostate cancer. We examined whether an association between 16 SNPs associated with circulating IGF-1 or IGFBP-3 concentrations and prostate cancer exists within subgroups defined by dietary protein intake in 5,253 cases and 4,963 controls of European ancestry within the NCI Breast and Prostate Cancer Cohort Consortium (BPC3). The BPC3 includes nested case-control studies within large North-American and European cohorts. Per-allele odds ratios for prostate cancer for the SNPs were compared across tertiles of protein intake, which was expressed as the percentage of energy derived from total, animal, dairy or plant protein sources, using conditional logistic regression models. Total, animal, dairy and plant protein intakes were significantly positively associated with blood IGF-1 (p < 0.01), but not with IGFBP-3 concentrations (p > 0.10) or with risk of prostate cancer (p > 0.20). After adjusting for multiple testing, the SNP-prostate cancer associations did not differ by intakes of protein, although two interactions by intake of plant protein were of marginal statistical significance [SSTR5 (somatostatin receptor 5)-rs197056 (uncorrected p for interaction, 0.001); SSTR5-rs197057 (uncorrected p for interaction, 0.002)]. We found no strong evidence that the associations between 16 IGF pathway SNPs and prostate cancer differed by intakes of dietary protein.